2009
DOI: 10.1161/circulationaha.109.875583
|View full text |Cite|
|
Sign up to set email alerts
|

Regulatory T Cells Modulate Postischemic Neovascularization

Abstract: Background-CD4ϩ and CD8 ϩ T lymphocytes are key regulators of postischemic neovascularization. T-cell activation is promoted by 2 major costimulatory signalings, the B7/CD28 and CD40 -CD40 ligand pathways. Interestingly, CD28 interactions with the structurally related ligands B7-1 and B7-2 are also required for the generation and homeostasis of CD4 ϩ CD25 ϩ regulatory T cells (Treg cells), which play a critical role in the suppression of immune responses and the control of T-cell homeostasis. We hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 37 publications
1
79
1
2
Order By: Relevance
“…Recent studies have suggested that regulatory T cells and NK cells may have a role in modulating postnatal neovascularization (41,42). Interestingly, in the hBMC-SCID/bg mouse model, a statistically significant difference in overall patency rates was not detected between BMC-seeded and unseeded scaffolds, which may be a reflection of the immunodeficient component of our mouse model.…”
Section: Expression) (C-e) Luminex Assaymentioning
confidence: 63%
“…Recent studies have suggested that regulatory T cells and NK cells may have a role in modulating postnatal neovascularization (41,42). Interestingly, in the hBMC-SCID/bg mouse model, a statistically significant difference in overall patency rates was not detected between BMC-seeded and unseeded scaffolds, which may be a reflection of the immunodeficient component of our mouse model.…”
Section: Expression) (C-e) Luminex Assaymentioning
confidence: 63%
“…By contrast, macropinocytosis might allow VEGFR2 signalling by fulfilling one or more of the above functions. It is tempting to speculate that macropinocytosis might be responsible for delivering signalling complexes of the receptor to downstream targets, such as ERK1/2 and Akt, that could reside at specific endosomal compartments (Dobrowolski and De Robertis, 2012;McKay and Morrison, 2007;Miaczynska et al, 2004;Platta and Stenmark, 2011;Schenck et al, 2008;Sorkin and von Zastrow, 2009;Teis et al, 2002;Zouggari et al, 2009). Consequently, macropinocytosis would link VEGFR2 to the downstream cascades required to regulate complex angiogenic responses, such as survival (Karali et al, 2014), proliferation and migration of endothelial cells (Herbert and Stainier, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of such T cell subsets in regulating collateral response to ischemia has been recently described. Using CD28-deficient mice that lack the Treg subset, or by depleting Tregs in wildtype animals by administering an anti-CD25 antibody, Zouggari and coworkers recently showed increased efficiency in blood flow recovery after femoral artery ligation [53]. The authors speculated that the suppressive effect of Tregs was due to their intrinsic inhibitory action on the effector immune cell response.…”
Section: Reviewmentioning
confidence: 99%